Utilization and metabolism of palmityl and oleoyl fatty acids and alcohols in caecal enterocytes of Atlantic salmon (Salmo salar L.) - Bogevik, Andre S; Olsen, Rolf E; Tocher, Douglas R (Aquaculture Nutrition, 2008)
The substitution of fish oil with wax ester-rich calanoid copepod-derived oil in diets for carnivorous fish, such as Atlantic salmon, has previously indicated a lower lipid digestibility. This suggests that the fatty alcohols (FAlc) present in wax esters may be a poorer substrate for intestinal enzymes than the fatty acids (FA) in triacylglycerol, the major lipid in fish oil. The hypothesis tested was that the possible lower utilization of dietary FAlc by salmon enterocytes is at the level of uptake and that subsequent intracellular metabolism was identical to that of FA. A dual-labelled FAlc-FA metabolism assay was employed to determine simultaneous FAlc and FA uptake and relative utilisation in enterocytes isolated from pyloric caeca of Atlantic salmon fed either a diet supplemented with fish oil or wax ester-rich Calanus oil. The diets were fed for 10 weeks before caecal enterocytes from each dietary group were isolated and incubated with equimolar mixtures of either [1-14C]16:0 FA and [9,10(n)-3H]16:0 FAlc, or [1-14C]18:1n-9 FA and [9,10(n)-3H]18:1n-9 FAlc. Uptake was measured after 2 h with relative utilization of labelled FAlc and FA calculated as a percentage of uptake. Differences in uptake were observed, with FA showing higher uptake than FAlc, and 18:1 chains a higher uptake than 16:0. A proportion of unesterified FAlc was possibly recovered in the cells, but the majority of FALc was recovered in lipid classes such as triacylglycerol and phospholipids indicating substantial conversion of FAlc to FA followed by esterification. However, incorporation of FA and FAlc into esterified lipids was higher when derived from FA than from FAlc. Twenty-five to fifty percentage of the absorbed 16:0 FA was recovered in TAG fraction of the enterocytes compared with fifteen to seventy-five percentage of 18:1 FA. Twenty to thirty percentage of the absorbed 16:0 FA was recovered in the PC fraction of the enterocytes compared with only five to fifteen percentage of the 18:1 FA. Less than 15% of the fatty chains taken up ...